The Cultural Significance and Order of Typical Courtyard Spaces in Shandong (Journal of Global Arts Studies, 2023)
Background: The residential courtyards in Shandong, characterized by their plain appearance and minimal decoration, are deeply rooted in the region's diverse natural conditions and profound local culture. The varied climate and topography of Shandong, along with its distinctive Qi-Lu culture, have shaped the unique characteristics of these courtyards. Objective: This study aims to uncover the distinctive features beneath the unassuming appearance of typical courtyards in urban and rural Shandong, and to interpret the deeper meanings behind their undecorated facades. Methods: Through an in-depth examination of the intrinsic connection between typical residential courtyards in Shandong and their spatial culture, this research combines literature review, field mapping, and image analysis. Extensive investigations were conducted across numerous towns and villages in Shandong Province, exploring the relationship between the form, distribution, and types of typical courtyards and regional culture. Results: The study reveals that the structural classification of courtyards aligns significantly with the regional divisions of the Northern Song Dynasty. Additionally, geographical features such as rivers, coasts, and mountains have a significant impact on the distribution of these courtyards. Conclusion: Typical residential courtyards in Shandong downplay external decoration, emphasizing an introspective and communal character. Their spatial layout underscores order, regulating family life and reflecting social relationships. The sustainable techniques employed in these courtyards subtly suggest a cultural ethos of "frugality nurtures virtue(Jian yi yang de)."
Keywords: Typical Courtyard; Shandong Residential Buildings; Spatial Order; Qi-Lu Culture